Survival Strategies of Indonesian Traditional Fisherman During The Paceklik or Famine Season - Sunartomo, Aryo Fajar; Sofia, Sofia; Gusti, Tito (Technium Social Sciences Journal, 2023)
Situbondo Regency is one of the regencies in East Java which has long coastline of 150 kilometers and large potential marine resources. With these geographic potential resources, most of the population work as traditional fishermen. However, in relation to the traditional fishermen, they are still trapped in a cycle of poverty because they still use traditional methods and tools to catch fish. In addition, natural factors that are uncertain and uncontrollable make fishermen in a poor condition. There are three objectives of the research, namely : 1). identifying the socio-economic characteristics of traditional fishing communities in Situbondo Regency, 2). identifying the factors that cause fishermen's poverty, 3) identifying survival strategies for traditional fishermen during the famine (paceklik) season. The research location was determined purposively, namely in the coastal community of Situbondo Regency with the consideration that in this place there are many traditional fishermen whose conditions are still poor. This research used a qualitative descriptive approach with a method of determining informants purposively as well. Data were collected by method of interview, observation and documentation, and then were analyzed by using Miles and Hubberman model. The results of the study show that 1) The fishermen in traditional fishing communities of Situbondo Regency have unique characteristics, namely they are mostly Madurese ethnic with no skills other than fishing. 2) There are four factors that cause poverty among traditional fishermen in the fishing community of Situbondo Regency, namely: factors of natural resources that are uncertain and difficult to be controlled, factors of low technology and traditional fishing gear, factors of human resources whose low qualities, and debt-loving culture. There are six survival strategies used when there is a famine season, namely: looking for side jobs or job diversification, optimizing the wife's role in productive work, strengthening social networks, reducing expenses on consumer goods, borrowing money or making debt to friends and relatives, and selling personal properties or bongings for getting some money.